Generation of a Soluble African Horse Sickness Virus VP7 Protein Capable of Forming Core-like Particles - Shani Bekker; Henk Huismans; Vida van Staden (Viruses, 2022)
A unique characteristic of the African horse sickness virus (AHSV) major core protein VP7 is that it is highly insoluble, and spontaneously forms crystalline particles in AHSV-infected cells and when expressed in vitro. The aggregation of AHSV VP7 into these crystals presents many problems in AHSV vaccine development, and it is unclear whether VP7 aggregation affects AHSV assembly or contributes to AHSV pathogenesis. Here, we set out to abolish VP7 self-assembly by targeting candidate amino acid regions on the surface of the VP7 trimer via site-directed mutagenesis. It was found that the substitution of seven amino acids resulted in the complete disruption of AHSV VP7 self-assembly, which abolished the formation of VP7 crystalline particles and converted VP7 to a fully soluble protein still capable of interacting with VP3 to form core-like particles. This work provides further insight into the formation of AHSV VP7 crystalline particles and the successful development of AHSV vaccines. It also paves the way for future research by drawing comparisons with similar viral phenomena observed in human virology.